Oman's relations with Bahrain and Kuwait (1744 - 1804) - Hashimy, Sa'id b. Muhammad (Journal of the Gulf and Arabian Peninsula Studies, 2000)
يهدف هذا البحث إلى إبراز نوع العلاقة بين عمان وبين البحرين والكويت خلال النصف الثاني من القرن الثامن عشر للميلاد .حيث كانت البحرين تابعة لعمان لمدة تزيد عن عشرين عاما اعتبارا من 1717، ولكن نتيجة للمشاكل التي اجتاحت عمان في مرحلة انهيار دولة اليعاربة ، وطموحات نادر شاه في الخليج ال أدت إلى خضوع البحرين للفرس . وكان على رأس السلطة في عمان في النصف الثاني من القرن 18م الإمام أحمد بن سعيد البوسعيدي الذي تم تنصيبه بعد انهيار دولة اليعاربة سنة 1749م . حكم أحمد بن سعيد عمان لمدة 34 سنة ، وشهدت فترة حكمه أحداث مهمة من استقرار آل صباح في الكويت وآل خليفة في الزبارة ثم انتقلوا إلى البحرين بعد فتحها عام 1783م . كما عاصر شموخ دولة كريم خان في إيران وتطلعه نحو البصرة ومحاصرتها أكثر من سنتين بين عامي 1775و1776م ، ودور أحمد بن سعيد في مساعـدة أهل البصرة في فك الحصار . واتصفت العلاقة بين الإمام أحمد والعتوب بأنها علاقة ودية وحميدة . وبعد وفاة الإمام أحمد بن سعيد عام 1783م ، اجتاحت عمان موجة من الاضطراب السياسي بين أبناء الإمام أحمد ، وتمخض عن ذلك تسوية بين الاخوة الثلاثة ، وآل أمر عمان إلى سلطان بن أحمد الذي رضى بمسقط عاصمة له . وبدأ نشاطه في ضم مجموعة من جزر الخليج وقاد طموحه نحو الاستيلاء على البحرين وتهديد الكويت ، لكن حاميته التي وطنها عام 1800م في البحرين لم تجد أرض صلبة بل ثار عليه آل خليفة ، بمساندة السعوديين .
Keywords: Politique étrangère -- Oman; Relations -- Oman -- Bahrein; Relations -- Oman -- Koweit; Vie politique -- Oman

State formation in Oman 1861-1970 - Hinā’ī, ʿAbd al-Malik al- (London School of Economics and Political Science (University of London), 2000)
The main hypothesis of this study is that in the period from the 1860s to the 1960s the politics and decision-making of the Omani state were influenced by four forces, namely the British, the merchants, the tribal leaders and the ulama. The arguments relate only to the Sultanate of Oman, since no reliable data are available for the Imamate of Oman. During the second half of the seventeenth century the Omani state entered its imperial age, which lasted until the middle of the nineteenth century. The Ya'ariba dynasty, which was the first ruling family in that age, was similar to the states described by Ibn Khaldun. This was followed by the rise of the Al Bu Said dynasty. The imperial age lasted until the collapse of the Omani empire in 1861. The main finding of this study are first that the British role was the most prominent in the formation of the post-imperial Omani state, while these of the merchants, the tribal leaders and the ulama were mostly indirect or minimal. Secondly, the study found that, in addition to the tribal conflict, the period between 1861 and the 1950s was dominated by two other forms of social struggle, namely conflict between the merchants and the peasants, and tensions in the fragile alliance between the tribal and religious leaders. Thirdly, the several types of external subsidy, which Oman started to receive after 1861, laid the foundation of the rentier state in Oman, much earlier than the oil era. Fourthly, the political division of Oman, which resulted from the Treaty of Sib of 1920, never led to the emergence of two independent states. The situation, which prevailed between 1920 and 1955, was to a large extent one of one state with two systems. It is hoped that, in addition to its contribution to the study of the history and international relations of Oman, this study will provide students of political economy with a better understanding of the nature of the Omani state as one of the oldest states in the Arab World.
Keywords: Vie politique -- Oman